Pendidikan Politik Gambut Bagi Perempuan di Kelurahan Kalampangan - Juli Natalia Silalahi; Osi Karina Saragih; Anisa Pebrianti; Jenni Hutasoit; Sugiarti Sugiarti (Jurnal Masyarakat Madani Indonesia, 2025)
The main focus of this community service activity is to make Kalampangan women the key actors in environmental sustainability, particularly in the management of peatland agricultural products. The role of political education on peatland aims to provide Kalampangan women with information and knowledge about peatland issues (from a political peatland perspective) so that they can actively protect peatlands, manage them for economic value, and ensure environmental sustainability. Another benefit is to enable women to contribute and participate in discussions for decision-making related to natural resource management from a gender perspective. The community service method used in this activity consists of four stages. The first stage involves conducting a socialization session titled “Peatland and Women: Issues, Impacts, and Initiatives.” The second stage of this community service activity is to form the “Women Caring for Peatland” group. The third stage is the symbolic tree planting as a form of commitment to peatland preservation. The final stage is the evaluation, which aims to assess the impact of the activity on participants' knowledge and awareness, as well as identify the challenges faced in the future management of peatland.